Improvement on the Nutritive Quality of Napier Grass Silage through Inoculation of Lactobacillus plantarum and Formic Acid - Saprilian Stya Hapsari; Suryahadi Suryahadi; Heri Ahmad Sukria (Faculty of Animal Science, Bogor Agricultural University, 2016)
The potential availability of forage feed is high, but in reality this potential has not been able to meet the requirement of feed both in sustainable quantity and quality. Silage made with the use of liquid fermentation additive (FA) can be a solution for those problems. The use of different levels of FA and addition of Lactobacillus plantarum bacteria as well as formic acid were expected to improve the nutritive quality of napier grass silage. The first experiment was designed to measure the fermentative quality of napier grass silage. The treatments used were the levels of FA, L. plantarum, and formic acid supplementations. The experiment used a completely randomized design with a 3x2x2 factorial arrangement with 3 replications. The first factor was the level of liquid FA (5%, 7.5%, and 10%), and the second factor was the inoculation of L. plantarum (without and with inoculation of the L. plantarum), and the third factor was the addition of formic acid (without and with the addition of 0.15% formic acid). The second experiment was aimed to evaluate chemical and microbiological characteristics, and in vitro digestibility of selected napier grass silage. The results showed that napier grass silage from all treatments showed good qualities. There were interactions between FA, L. plantarum, and formic acid on DM content (P<0.05) and ammonia production (P<0.01). The use of FA showed an interaction (P<0.01) with the addition of L. plantarum and formic acid in Fleigh point. Ammonia production in rumen (P<0.01), total VFA (P<0.05), and in vitro digestibility (P<0.01) were significantly affected by the treatments. The optimal level of liquid FA was 7.5%. Based on the nutritive quality of silage, L. plantarum addition was as effective as control treatment to improve nutritive quality of napier grass silage through the increased of fermentation characteristics i.e., low pH, high DM product, high fermentation product (VFA), and digestible on rumen. Formic acid reduced ammonia production during ensiling and fermentation in rumen, but it was less effective in inhibiting the fermentation process when it was combined with L. plantarum.